2019
DOI: 10.1007/s40123-019-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual, Refractive and Ocular Surface Outcomes Between Small Incision Lenticule Extraction and Laser-Assisted In Situ Keratomileusis for Myopia and Myopic Astigmatism

Abstract: Laser-assisted in situ keratomileusis (LASIK) is the most commonly performed laser refractive surgical technique worldwide for the treatment of myopia and myopic astigmatism. In recent years, small incision lenticule extraction (SMILE) has emerged as a promising alternative to LASIK, requiring only a single femtosecond laser to create an intrastromal lenticule, which is then removed via a small incision. The technique obviates the need for a corneal flap. A number of published studies have compared the two tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…Lau et al recently reviewed 22 recent studies comparing the clinical outcomes in LASIK and SMILE for myopia and myopic astigmatism. They found that the two techniques are comparable; SMILEtreated eyes experienced lower severe postoperative dry eye symptoms and faster recovery of corneal sensitivity while LASIK-treated eyes experienced faster recovery of visual acuity (Lau et al, 2019).…”
Section: Corneal Stromal Lenticule Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lau et al recently reviewed 22 recent studies comparing the clinical outcomes in LASIK and SMILE for myopia and myopic astigmatism. They found that the two techniques are comparable; SMILEtreated eyes experienced lower severe postoperative dry eye symptoms and faster recovery of corneal sensitivity while LASIK-treated eyes experienced faster recovery of visual acuity (Lau et al, 2019).…”
Section: Corneal Stromal Lenticule Transplantationmentioning
confidence: 99%
“…Damgaard et al suggested that prior corneal crosslinking (CXL) induction of SMILE-derived lenticules may reduce time to refractive stabilization, but it also requires longer postoperative steroid treatment (Damgaard et al, 2019). However, additional research is needed to confirm if the additional CXL step reduces the incidence of iatrogenic keratectasia (Lau et al, 2019).…”
Section: Corneal Stromal Lenticule Transplantationmentioning
confidence: 99%
“…So, the accurate calculation of IOL power for these patients would be very important soon. Small incision lenticule extraction (SMILE) surgery was firstly reported by Sekundo [2] and Shah [3] in 2011, it is popular for excellent visual outcomes, superior biomechanics, faster recovery of dry eye and corneal nerve reinnervation [4]. Over 2 million patients have undergone SMILE, including 1 million Chinese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond LASIK (FS-LASIK) is the most popular laser refractive surgery with established safety and efficacy. 1 Recently, small incision lenticule extraction (SMILE) was approved by the US Food and Drug Administration for myopic correction up to –10.0 diopters and myopic astigmatism up to –3.0 diopters. Compared with FS-LASIK, SMILE protects from traumatic flap displacement risk using a 2-mm stromal incision.…”
mentioning
confidence: 99%
“…However, studies have reported slower recovery of visual acuity after SMILE than that after FS-LASIK, even with laser-scanning pattern optimization. 1 , 2 , 9 Ang et al 10 reported that postoperative symptoms, such as fluctuation and occasional blurring of vision, were more significant at 1-month postoperation for SMILE than for FS-LASIK. As an elective surgical procedure to restore uncorrected visual acuity and improve quality of life, delayed recovery after SMILE may affect patient satisfaction.…”
mentioning
confidence: 99%